1977
DOI: 10.1017/s0043174500033075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrazine on Soybean Tolerance to Metribuzin

Abstract: Atrazine [2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine] at 0.14 kg/ha and metribuzin [4-amino-6-tert-butyl-3-(methylthio)-as-triazin-5(4H)one] at 0.56 kg/ha applied under field conditions interacted synergistically to reduce soybean [Glycine max(L.) Merr. ‘Harsoy-63′] growth. In the greenhouse, a number of combinations with atrazine at 0.07 kg/ha or greater and metribuzin at 0.56 kg/ha and greater interacted synergistically to reduce soybean fresh and dry weights 30 days after planting. Over a soil pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…of Florida, Gainesville, FL 32611, respectively. metri buzin [ 4-amino-6-ter t-bu ty 1-3-(meth y lthio )-as-triazine-5(4H)-one], an herbicide widely used for soybean weed control, has been observed (7). This synergism resulted in much greater soybean :phytotoxicity than would be expected from the additive effect of the atrazine and metribuzin.…”
mentioning
confidence: 99%
“…of Florida, Gainesville, FL 32611, respectively. metri buzin [ 4-amino-6-ter t-bu ty 1-3-(meth y lthio )-as-triazine-5(4H)-one], an herbicide widely used for soybean weed control, has been observed (7). This synergism resulted in much greater soybean :phytotoxicity than would be expected from the additive effect of the atrazine and metribuzin.…”
mentioning
confidence: 99%
“…Although Ladlie et al (1977) reported that tank mixing trifluralin with metribuzin significantly reduced root uptake of metribuzin by soybean seedlings, tank mixing with trifluralin at the Saskatoon site did not significantly affect the magnitude of metribuzin residues in the green foliage of faba bean. Consequently, residue data for metribuzin, whether applied singly or as a tank mixture, were combined for the 0.28 and 0.42 kg ha -1 application rates at this site.…”
mentioning
confidence: 81%
“…Spectrophotometrically obtained values were reported to be 0.99 [45], 1.1 [46] and 1.0 [47]. The latter authors [47] dissolved metribuzin in methanol where the alcohol adds to the azomethine bond even more strongly than water, and forms an j-adduct.…”
Section: Acid-base Reactionsmentioning
confidence: 99%